2022
DOI: 10.3390/cancers14081974
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes of Laparoscopic Pelvic Lymph Node Debulking during Staging Aortic Lymphadenectomy in Locally Advanced Cervical Cancer: A Multicenter Study

Abstract: Background: Few studies have evaluated laparoscopic pelvic lymph node (PLN) debulking during staging aortic lymphadenectomy in locally advanced cervical cancer (LACC). It allows us to know the lymph node status and facilitates the action of chemoradiotherapy (CRT) by reducing tumor burden. We evaluated its feasibility and compared the perioperative morbidity and the time to CRT with a control group. Methods: This was a multicenter retrospective study of patients with LACC FIGO stage IIIC1r who were recipients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…They concluded that indeed, it is feasible to perform laparoscopic pelvic LND in the same procedure as aortic LND in LACC without increasing surgical complications. Additionally, this procedure allows the clinician to know the lymph node status without delaying start of treatment with CRT [26]. The impact on survival, however, is not discussed.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that indeed, it is feasible to perform laparoscopic pelvic LND in the same procedure as aortic LND in LACC without increasing surgical complications. Additionally, this procedure allows the clinician to know the lymph node status without delaying start of treatment with CRT [26]. The impact on survival, however, is not discussed.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also known that bulky lymph nodes require high-dose boosted external beam radiotherapy (EBRT) to become sterilized. To date, the available evidence concerning the impact of debulking surgery on bulky lymphatic disease provides heterogeneous results, with some studies favoring the technique [ 44 , 45 ] and others providing evidence against it [ 43 , 46 , 47 ]. A prospective phase III randomized trial (CQGOG0103) will help provide more information on this group of patients; however, its results are not anticipated within this decade as the enrollment will last four years and the follow-up will be completed at five years [ 48 ].…”
Section: Advanced-stage Disease Challengesmentioning
confidence: 99%
“…Removing the bulky lymph nodes might improve the chance of completely sterilizing by CCRT and reduce the toxicity caused by higher dose of radiation. Some studies demonstrated improved survival after bulky nodal resecting [ 9 17 ], while others showed no survival benefit from nodal resection in cervical cancer with bulky lymph node [ 18 19 20 ]. However, almost of the studies are retrospective with the limitations, such as without unified action protocol for nodal surgery and boosting, enrollment spanned long time and insufficient quantity.…”
Section: Introductionmentioning
confidence: 99%